Association of Cytomegalovirus (CMV) Infection with Guillain- Barré Syndrome (GBS) In Tertiary Care Hospital (BSMMU) of Bangladesh - Eusuf, Nuruddin Mohammad; Khan, Md Rezaul Karim; Rizvi, Abu Nasir; Kader, Sheikh Abdul; Md Salahuddin, Abu Jafor; Zahid, Rashed Imam; Patwary, Khairul Kabir; Hasan, Mohammad Sayeed; Md Kabiruzzaman, -; Alim, Md Abdul; et al. (Bangladesh Journal of Neuroscience, 2013)
Background: Guillain-Barré syndrome (GBS) usually preceded by infections, in particular cytomegalovirus (CMV). It may occur by primary infection, reinfection or by reactivation of CMV. Objective: The aim of the present study was to evaluate the association of Guillain-Barré syndrome (GBS) with Cytomegalovirus (CMV) infection. Methodology: This case control study was carried out in the indoor and outpatient Department of Neurology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from 1st January 2010 to 31st December 2011 for the duration of two years. All patients with GBS, who attended in neurology OPD or inpatient department at BSMMU during the study period, fulfilling the inclusion and exclusion criterias were included in this study. Age & sex matched volunteers, patients attendants, patients other than GBS who were nondiabetic, had no renal or hepatic diseases or family history of polyneuropathy were included in control group. Results: A total number of 78 respondents of which 39 patients were taken as cases and rest 39 were taken as controls who appeared in neurology OPD or inpatient department at BSMMU during the study period, fulfilling the inclusion and exclusion criterias were included in this study. The mean age ± SD of case and control groups were 30.82 ± 12.56 and 31.00 ± 12.77 years respectively (p=0.950). In case group the history of respiratory tract infection was present in 46.2% cases and absent in control group (p=0.001). In case group the history of gastroenteritis was present in 28.2% cases and absent in control group (p=0.001). In case group the history of fever was present in 30.8% cases and absent in control group (p=0.001). Anti-CMV IgM antibody was positive in 5.1% cases. Four fold rise of IgG in case group was present in 10.3% cases and absent in control group (p=0.040). Confirmed CMV infected GBS cases were 15.4% and absent in control group (p=0.011). Conclusion: The findings of this study permit to conclude that there is a significant association of Guillain-Barré syndrome (GBS) with Cytomegalovirus (CMV) infection. Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 88-97